Unraveling Discursive Strategies And Polarized Ideology: A Critical Discourse Analysis Of The Indo-Pacific Strategy Of The Whitehouse - Mamona Yasmin Khan , Zoha Khan (Migration Letters, 2024)
The present study aims to examine the use of discursive strategies and polarized ideology employed by the United States of America in the Indo-Pacific Strategy of the Whitehouse shedding light on the underlying power dynamics and political implications surrounding this strategic approach. For this purpose, van Dijk (2006b) and van Dijk (1998) were used as theoretical framework. van Dijk (2006b) has provided a list of discourse structure that investigate ideology present in discourse whereas van Dijk (1998) has presented an ideological framework that reveals the manner in which the ingroup is presented positively and outgroup is depicted in a negative manner. Five discursive strategies were picked along with the ideological square model to formulate the analytical framework. These strategies were categorization, lexicalization, polarization, negative other-representation and positive self-representation. The findings of the research revealed that the US has employed different discourse structures several times to propagate its ideology. Moreover, it was found out the political polarization created as a result of these discursive strategies depicted the US ideology as positive whereas China is displayed as an opposing belief system which is negative and harmful.